(untitled) - Kant, Immanuel (Cambridge [England], 2004)
This new, revised edition of Kant's Prolegomena, which is the best introduction to the theoretical side of his philosophy, presents his thought clearly by paying careful attention to his original language. Also included are selections from the Critique of Pure Reason, which fill out and explicate some of Kant's central arguments (including famous sections of the Schematism and Analogies), and in which Kant himself explains his special terminology. The first reviews of the Critique, to which Kant responded in the Prolegomena, are included in this revised edition.
Keywords: Knowledge, Theory of,Metaphysics,Kiến thức, Lý thuyết,Siêu hình học